255 New Zealand super rugby injury surveillance: match injuries from 2015–2018. (3rd March 2020) - Salmon, Danielle; Murphy, Ian; Quarrie, Kenneth; MacLeod, Greg; Singh, Asheer; Letts, Adam; Roche, John; Robinson, Deborah; Swan, Martin; Dorfling, Theo; Shaw, Cameron; Rottier, Katherine; et al.
Abstract : Background: Rugby union is a collision-based sport, as such the occurrence of injuries resulting in time-loss from participation is inevitable. In 2015 New Zealand Rugby (NZR) began an injury surveillance program with all NZ-based Super Rugby teams to capture all time-loss injuries. Objective: To examine the incidence, burden, severity, nature and cause of match injuries in NZR Super Teams. Design: A prospective observational study. Setting: Match injuries sustained during the 2015–2018 Super rugby seasons. Patients (or Participants): All contracted rugby players (n=190) over the four seasons. Main outcome measurements: Primary outcomes of interest were incidence (injuries/1000 player match-hours), injury burden (days absence/1000 player-match-hours), median severity (days absence), location (%), diagnosis (%) and mechanism (%). Results: From 2015–2018 the following incidence was documented 122, 85, 94 and 81 injuries/1000 player-match-hours respectively. During the first year the initial injury incidence was 122 injuries/1000 player-match-hours, which was significantly higher than 2018, 81 injuries/1000 player-match-hours. The days absence increased over the period from a median of 7 days missed in 2015 (burden: 2262 days absence/1000 player-match-hours) to 16 in 2018 (burden: 3206 days absence/1000 player-match-hours). There was a significant difference in the incidence of injury by position, where forwards sustained 106 injuries/1000 player-match-hours and backs 85. The most at risk position was the hooker (118 injuries/1000 player-match-hours) and the lowest inside backs (59 injuries/1000 player-match-hours). Tackling was the most common mechanism of injury 27%, followed by being tackled 25% and collisions 12%. The head was the most common injury location (19%), followed by the shoulder (13%) and knee (10%). The three most commonly diagnosed injuries were sprains (28%), concussions (20%) and muscle rupture/strains/tear/cramp (16%). Conclusions: The current data supports the international trend in professional rugby where the time-loss associated with each injury is increasing, resulting in higher levels of injury burden.